2012
DOI: 10.7314/apjcp.2012.13.12.6097
|View full text |Cite
|
Sign up to set email alerts
|

ABO and Rh Blood Groups and Risk of Colorectal Adenocarcinoma

Abstract: Background: Previous studies have observed an association between ABO blood group and risk for certain gastrointestinal malignancies, including pancreatic and gastric cancer. However, it is unclear whether there is such an association with colorectal cancer (CRC). In this study, possible relationships between ABO blood groups and Rh factor and KRAS status in patients with CRC were investigated. Materials and Methods: In 1,620 patients with CRC, blood group and Rh factor were examined and compared with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
3
31
0
1
Order By: Relevance
“…The association between blood group type and CRC risk has rarely been investigated. To date, only one case-control study has reported an association between blood group type O and CRC risk [ 27 ]. However, our study revealed that only MSH2 germline mutation carriers with blood group B exhibited an increased CRC risk (HR = 2.64, 95% CI = 1.06–6.58).…”
Section: Discussionmentioning
confidence: 99%
“…The association between blood group type and CRC risk has rarely been investigated. To date, only one case-control study has reported an association between blood group type O and CRC risk [ 27 ]. However, our study revealed that only MSH2 germline mutation carriers with blood group B exhibited an increased CRC risk (HR = 2.64, 95% CI = 1.06–6.58).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have reported an association between ABO blood group and the risk of various epithelial cancers. Non-O blood group increases risk of cancer including pancreatic, gastric, ovarian, kidney, colorectal and skin carcinomas (Wolpin et al, 2009;Edgren et al, 2010;Xie et al, 2010;Joh et al, 2012;Poole et al, 2012;Urun et al, 2012). Similarly, the thrombosis was associated with both increased risk of cancer and advanced disease and poor prognosis (Chew et al, 2006;Ahlbrecht et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ABO blood group gene is mapped at the chromosome 9q34, in which the genetic alterations are common (Humphray et al, 2004). The correlation of ABO blood groups with certain disease including infections, vascular, and malignant diseases has been shown (Hakomori, 2001 (Wolpin et al, 2009;Edgren et al, 2010;Joh et al, 2012;Poole et al, 2012;Urun et al, 2012). However, the data on the role of ABO blood group and Rh factor in lung cancer is limited and inconsistent (Alvarez-Fernandez and Carretero-Albinana, 1991;Lee et al, 1991;Cerny et al, 1992;Miyake et al, 1992;Gwin et al, 1994;Rice et al, 1995;Graziano et al, 1997;Ulger et al, 2002;SanchezMora et al, 2007;Suadicani et al, 2007;Leon-Atance et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In similarly, in other study it was found that the A blood group was associated with a modestly increased ovarian cancer risk compared to blood group O [6]. Also it was found that there were statistically significant difference between patients and controls with respect to O vs. non O blood group [7]. Glioblastoma (GBM) is the most common type of primary brain tumor.…”
Section: Introductionmentioning
confidence: 78%